Epithelioid sarcoma of the hand mimicking Dupuytren's disease: A case report and review of the literature - Athanasios Papas; Ioannis Kaloudis; Stavroula Pervana; Eleni Georgiadou; Theodoros Garoufalias; Dimitrios Dionyssiou; Efterpi Demiri (JPRAS Open)
ABSTRACT: We report a case of recurrent epithelioid sarcoma in a 30-year-old man whose initial clinical and histological findings were compatible with Dupuytren's contracture. Lymph node spread, distant metastases, and targeted histological examination eventually led to a correct diagnosis. Epithelioid sarcoma should always be considered in the differential diagnosis of Dupuytren's disease, particularly in young patients with recurrent disease. Level of evidence: V